A quantitative analysis of out-of-hospital pediatric and adolescent resuscitation quality – A report from the ROC epistry-cardiac arrest. (August 2015) - Sutton, Robert M.; Case, Erin; Brown, Siobhan P.; Atkins, Dianne L.; Nadkarni, Vinay M.; Kaltman, Jonathan; Callaway, Clifton; Idris, Ahamed; Nichol, Graham; Hutchison, Jamie; Drennan, Ian R.; Austin, Michael; et al.
Abstract: Aim: High-quality cardiopulmonary resuscitation (CPR) may improve survival. The quality of CPR performed during pediatric out-of-hospital cardiac arrest (p-OHCA) is largely unknown. The main objective of this study was to describe the quality of CPR performed during p-OHCA resuscitation attempts. Methods: Prospective observational multi-center cohort study of p-OHCA patients ≥1 and <19 years of age registered in the Resuscitation Outcomes Consortium (ROC) Epistry database. The primary outcome was an a priori composite variable of compliance with American Heart Association (AHA) guidelines for both chest compression (CC) rate and CC fraction (CCF). Event compliance was defined as a case with 60% or more of its minute epochs compliant with AHA targets (rate 100–120 min −1 ; depth ≥38 mm; and CCF ≥0.80). In a secondary analysis, multivariable logistic regression was used to evaluate the association between guideline compliance and return of spontaneous circulation (ROSC). Results: Between December 2005 and December 2012, 2564 pediatric events were treated by EMS providers, 390 of which were included in the final cohort. Of these events, 22% achieved AHA compliance for both rate and CCF, 36% for rate alone, 53% for CCF alone, and 58% for depth alone. Over time, there was a significant increase in CCF ( p < 0.001) and depth ( p = 0.03). After controlling for potential confounders, there was no significant association between AHA guideline compliance and ROSC. Conclusions: In this multi-center study, we have established that there are opportunities for professional rescuers to improve prehospital CPR quality. Encouragingly, CCF and depth both increased significantly over time.